Effectiveness of the Peer Educator Model in Improving Hemoglobin Level among Adolescent Girls in Depok City - Nurmadinisia, Rahmi; Susilawati, Susilawati (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Anemia remains a global public health concern due to its high prevalence among adolescent girls and women of reproductive age. According to the 2022 Indonesian Health Survey, the prevalence of anemia among adolescent girls was 23%. Hemoglobin (Hb) testing conducted by the Depok City Health Office revealed  that 9,514 (36.34%) students were found to be anemic. Objective: This study aimed to determine the effectiveness of the peer educator model in improving hemoglobin levels among adolescent girls in Depok City. Methods: This study employed a prospective cohort design with a quantitative quasi-experimental pretest-posttest approach. The study was conducted among 11th and 12th grade female students at Raflesia IT High School, Depok. A total of 63 participants were included in the study. Hemoglobin levels were measured before and after the intervention, which involved peer education-based health education and mentoring on anemia prevention.  Results: The peer educator model effectively increased hemoglobin levels among the participants. A significant improvement in mean Hb levels was observed after the intervention (p=0.015). Conclusion: The peer educator model was  proven effective in improving hemoglobin levels among adolescent girls. Training non-anemic students as peer educators is recommended to enhance peer-to-peer support and education in anemia prevention programs.